2020
DOI: 10.3390/cells9081755
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor—14 Acts as Tumor Suppressor in Lung Adenocarcinomas

Abstract: Investigation of the molecular dynamics in lung cancer is crucial for the development of new treatment strategies. Fibroblast growth factor (FGF) 14 belongs to the FGF family, which might play a crucial role in cancer progression. We analyzed lung adenocarcinoma (LUAC) patients samples and found that FGF14 was downregulated, correlating with reduced survival and oncogenic mutation status. FGF14 overexpression in lung cancer cell lines resulted in decreased proliferation, colony formation, and migration, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Of note, a recent study reported that FGF12 (the homologue of FGF14 [30]) have a malignancy-inhibitor effect on pancreatic cancer cell lines [31]. Two most recent studies reported that FGF14 overexpression leads to tumor suppressive effects in lung adenocarcinoma and nasopharyngeal carcinoma [32,33]. In line with the previous in-vitro…”
Section: Discussionsupporting
confidence: 74%
“…Of note, a recent study reported that FGF12 (the homologue of FGF14 [30]) have a malignancy-inhibitor effect on pancreatic cancer cell lines [31]. Two most recent studies reported that FGF14 overexpression leads to tumor suppressive effects in lung adenocarcinoma and nasopharyngeal carcinoma [32,33]. In line with the previous in-vitro…”
Section: Discussionsupporting
confidence: 74%
“…Another factor that regulates COL11A1 expression is Fibroblast Growth Factor-14 (FGF-14). FGF-14 is downregulated in lung adenocarcinoma patient samples [ 61 ], and the overexpression of FGF-14 in the lung adenocarcinoma cell line A549 results in downregulation of COL11A1 expression.…”
Section: Col11a1 Signalingmentioning
confidence: 99%
“…Furthermore, in breast cancer patients receiving radiochemotherapy (5-fluorouracil, vinorelbine, radiotherapy), FGFR1 expression correlated with good response to treatment, whereas FGFR1-negative cancers showed resistance to this treatment [ 252 ]. Additionally, the reduced FGF14 level was correlated with poor survival and oncogenic mutation status (e.g., KRAS, EGFR) in lung adenocarcinoma (LUAC) patients [ 253 ]. Overexpression of FGF14 in NSCLC LUAC cell line (A549) resulted in decreased proliferation, colony formation and migration, and enhanced mesenchymal to epithelial transition, indicating that FGF14 reduces the invasiveness of lung cancer cells in vitro while ablation of FGF14 in these cells reversed the above changes, supporting its suppressive role in lung cancer progression.…”
Section: Enhancement Of Chemotherapy By Fgfs/fgfrs Actionmentioning
confidence: 99%